Stratifikasi Sosial Pada Keluarga Yang Nafkahnya Ditanggung Istri (Studi Kasus di Kelurahan Kedungbunder Kabupaten Blitar) - Lukman Budi Santoso; Moh. Alfin Sulihkhodin (Jurnal Intervensi Sosial dan Pembangunan, 2022)
The phenomenon of wives working today is considered to cause changes and shifts in roles in a family. The position that generally places a husband as the head of the family and the main breadwinner, seems to have slowly changed. Its not as different as happened in some families in Kedungbunder Village Blitar Regency, where only the figure of the wife works to provide for the family. This kind of condition puts a wife having a more dominant role in the family. This study was conducted with the aim of examining social stratification among families whose livelihoods are borne by the wife. The method used is a qualitative research approach (field research), where data is collected through an in-depth interview process and parsipatory observation. The results showed that, some families in Kedungbunder Blitar Village where only the wife is working show the rule of law that states that the husband is the head of the family and the wife as a housewife, are considered not always applicable in the existing social reality. In the family, the wife's position is in a high social class because it is the economic source of the family and has more dominant power than other family members.Keywords: Social Stratification, Family, The Wife Works